The International Student Experience at the University of Nottingham, UK Campus: A study of the impact of internationalisation on current students at a ‘global’ university - Hutchinson, Lindsay (2011)
n the last four decades the internationalisation of higher education has risen in prominence in the strategies, aims and activities of higher education institutions across the world. One particular internationalisation activity, internationalisation at home, refers to the international experience which can be gained by those students who do not take part in an international mobility scheme but who live and work among a diverse student community on their home campus. In recent years several research studies have been carried out in this area at higher education institutions around the world. However, despite the prominence of internationalisation at the University of Nottingham and the rich diversity of the student community on the UK campus, little research has been carried out to ascertain the amount and quality of international experience current Nottingham students are gaining. This study sought to investigate whether current students at Nottingham were gaining an international experience, what level of importance they placed on this concept, if any barriers existed in the academic or social life of the University which were hindering international experience, and if examples of best practice could be found for further development. This study found that although current students are able to identify international experience gained while studying at Nottingham, these experiences are limited and the value placed on them is minimal in many cases. It is recommended that more should be done to articulate the value of an international experience to students both prior to and after arrival at Nottingham. Examples of best practice have been identified alongside several institutional and general barriers which should be addressed at every level of the University if the opportunities available at Nottingham are to be fully realised for the benefit of current students.